24.9k views
2 votes
4(x - 1) + 5x = 6x - 16
Please help me solve the equation

User SQB
by
5.2k points

2 Answers

4 votes

Answer:

4x-4+5x=6x-16, 9x-4=6x-16, 3x=-12, x=-4

Explanation:

User Atia
by
5.7k points
4 votes

Answer:

x=−4

Explanation:

Step 1: Simplify both sides of the equation.

4(x−1)+5x=6x−16

(4)(x)+(4)(−1)+5x=6x+−16(Distribute)

4x+−4+5x=6x+−16

(4x+5x)+(−4)=6x−16(Combine Like Terms)

9x+−4=6x−16

9x−4=6x−16

Step 2: Subtract 6x from both sides.

9x−4−6x=6x−16−6x

3x−4=−16

Step 3: Add 4 to both sides.

3x−4+4=−16+4

3x=−12

Step 4: Divide both sides by 3.

3x/3=-12/3

x=-4

User VanagaS
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.